Visual analogue score and endoscopic domain analysis to assess the outcome of microdebrder in sinonasal diseases - Harugop, Anil S.; Padmavathy, O.; Bellad, Shama A.; Ramesh, Reshma; Havaldar, Rajesh R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The use of microdebrider in various sinonasal diseases have been sparingly understood. The present study aims to find out the effectiveness of a microdebrider in different sinonasal diseases by using each domain of visual analogue scale (VAS) and confirming the findings by diagnostic nasal endoscopy. Methods: A prospective observational study was done among patients with sinonasal disease between January 2019 to March 2020 in our tertiary care hospital. A subjective visual analogue scale (VAS) was completed by every patient for all domains according to Lund and Mackay symptom scoring system. Using Lund Kennedy scoring, polyp, edema and discharge were assessed preoperatively. Patients were followed up for 1 week, 6 weeks and 3 months. At 3 months both VAS and Lund Kennedy scoring was done. Post operatively scarring and crusting were assessed separately. Results: There was a significant improvement in domains post operatively in all the diseases considered (p=0.001). In Lund Kennedy endoscopic scoring system there was significant improvement in all the domain that was taken into consideration (p=0.001). Inter-disease domain comparison was also made. Conclusions: The study substantiates the use of microdebrider in various sinonasal disease. Microdebrider being a modern multipurpose instrument plays a significant role in complete clearance of the disease with good postoperative outcome.